Business pitching criteria in evaluating potential Youthpreneurs / Dg Kamisah AB, Rozita @ Uji Mohammed, Cyril Supain, Falex J. Langkan - Ab, Dayang Kamisah; Mohammed Cyrill, Rozita@uji; Langkan, Falex J.
Traditionally, potential or would-be entrepreneurs have been assessed through their Business Plan, which consists of Administrative Plan, Operational Plan, Marketing plan and Financial Plan. However, most of the grant providers nowadays require would-be entrepreneurs to pitch their idea. Business pitching is considered as a platform to get funding. Thus, would-be entrepreneurs should have good communication skills as well as persuasion skills in finding a grant that suits their business goals. Universities and other educational institutions are expected to produce graduate students who are well equipped with entrepreneurial mindset and skills. Students are exposed to entrepreneurship courses which aim to increase their understanding and skills in that field. One of the tasks given to them is doing an individual presentation regarding the idea and business that they want to introduce. A few criteria is used to evaluate their competency and capability in presenting their ideas. This study focuses on youthpreneurs which refers to business owners between the ages of 15 and 35 years. Tools to evaluate capabilities of potential youthpreneurs used criteria provided by the university, which include the introduction of the business idea, the content of the presentation, defense ability, fluency and clarity, effective audio visual, non-verbal communication and time management. One of the challenges for the would-be entrepreneurs to start-up their business is a lack of financial resources. They are wondering about how to get funding to start a business, and most of them quickly realize that the financing process is rarely simple or straightforward. In relation to this issue, government agencies have provided a number of grants to assist and encourage individuals to become an entrepreneur. Apart from government grants, there are also some available grants from the economic development agencies as well as private sources. In Malaysia, a few grants have been introduced such as Rural Business Challenge (RBC), Bumiputera Entrepreneurs Start-up Scheme (SUPERB), Tunas Usahawan Belia Bumiputera (TUBE) and SATA PitchBorneo. These grants are also to encourage community development and also establishing environmentally friendly businesses. In order to get the grant, individuals have to pitch their idea and convince the grant providers to give their support. This paper aims to evaluate potential youthpreneurs through business pitching criteria and to identify the ability of doing pitching based on gender and faculty.